Hospital Waste and Cleaning Workers in Baquba Teaching Hospital - Shahab A Al-Azzawi (Diyala Journal of Medicine, 2019)
Background: Medical waste is potentially hazardous, infectious, and toxic materials. It therefore requires special handling and disposal practices.